The Application Roundtable Technique for Teaching Descriptive Text at SMK Jambi Medan - Lastri Wahyuni Manurung; Sondang Manik; Riniwati Sembiring; Rotua Elfida (JURNAL ABDIMAS MADUMA, 2022)
Writing is more than a medium of communication. It means that writing is not just a way to communicate with each other but also a means of ideas and emotional expression (Raymond, 1980).Writing makes words permanent, and thus expands the collective memory of human beings. Spoken words disappear as soon as they are spoken, but writing freezes their thoughts and makes them visible and permanent so people can examine and test their quality.students gotdifficulty starting the writing, they got confused about what to write and also about how to generate ideas. This is because the lack of knowledge about the steps in writing was a procedural factor that cause difficulties for all students. And the most important thing is that writing usually getsthe least attention in teaching learning in the classroom, which makes students rarely exposed to writing.This matter might happen because acquiring writing skills needs a lot of practice, and producing a piece an essay needs a long process. Most researchers recognize this difficulty in writing is caused by the complexity of writing. roundtable teaching technique is a technique that requires a group or team working in the teaching learning process which requires all members to know and be ready to explain their group’s answer(s), when students help their group mates, they help themselves and their whole group, because the response given belongs to the whole group, not just to the group member giving it. Roundtable is a technique designed with a round table form that divides the students into groups with their respective tasks and allows students to work or solve problems by working together in which each member in the group has each task and then the results obtained from the task they have done will be collected and solved simultaneously. Key Words : Roundtable Technique, Descriptive Text